Optimization of On-Grid Solar Power System Planning at Plaza Asia Tasikmalaya Using HOMER - Agustian, Doni; Sutisna, Sutisna; Faridah, Linda (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2025)
This study presents a comprehensive techno-economic planning of an On-Grid Photovoltaic Power Plant (PV PP) system for Plaza Asia Tasikmalaya by utilizing the HOMER (Hybrid Optimization Model for Multiple Energy Resources) software. The main objective is to develop an optimized PV system configuration based on actual load profiles and solar radiation data, without focusing on physical implementation or post-installation impacts. The planning process includes site-specific energy demand analysis, assessment of solar potential using satellite-derived datasets, and the selection of system components such as photovoltaic panels, battery storage, and inverters. Field observations and documentation were conducted to collect primary and secondary data regarding electricity consumption trends, solar irradiance levels, and component specifications and prices. The simulation using HOMER indicates that the optimal system configuration comprises 1,894 units of 340 Wp monocrystalline solar panels, 102 EnerSys PowerSafe SBS 1800 battery units (248 kWh), and 50 SolaX X3-Hybrid10 inverters rated at 10 kW. The system is projected to generate 902,334 kWh annually, supplying approximately 62.1% of the total electricity consumption of the building. The remaining demand is met by the PLN grid, especially during periods of low irradiance or peak loads. The simulation yields key performance indicators including Net Present Cost (NPC), Initial Capital Cost, and Levelized Cost of Energy (COE), which are calculated by HOMER using discounted cash flow principles. These indicators are crucial in evaluating the technical and financial feasibility of the planned configuration. By focusing on accurate simulation, real-world data inputs, and economically viable system design, this study contributes a replicable planning approach for renewable energy integration in commercial buildings. It also highlights the importance of using simulation tools like HOMER in supporting investment planning, technology selection, and policy formulation related to on-grid solar energy systems. The findings may serve as a technical reference for future energy planning in similar commercial settings across regions with comparable solar resources.